2004
DOI: 10.1002/jmor.10277
|View full text |Cite
|
Sign up to set email alerts
|

Functional morphology of the ear in fossorial rodents, Microtus arvalis and Arvicola terrestris

Abstract: Functionally relevant features and parameters of the outer, middle, and inner ear were studied morphologically and morphometrically in two species of voles, smaller Microtus arvalis and larger Arvicola terrestris. The findings in these fossorial (i.e., burrowing) rodents with components of surface activity were compared with respective findings reported for taxonomically related muroid rodents representing the same size classes but different eco-morphotypes: obligate subterranean rodents (Ellobius talpinus and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 34 publications
5
37
0
Order By: Relevance
“…A number of studies carried out on the vascularization of middle ear did not report the presence of stapedial artery; however, its presence was determined in this study and some other studies on certain mammal species like a mongolian gerbil (Rosowski et al, 1999), rats (Ortug, 2001;Yamamoto et al, 2003), fossorial rodents (Lange et al, 2004), and Talpid moles (Mason, 2006). Lange et al (2004) and Ortug (2001) observed that stapedial artery passing through intercrural foramen was surrounded by an osseous canal. Ortug (2001) also reported that the artery continued in such a canal in the middle ear cavity after exiting from the foramen.…”
Section: Anatomy and Arterial Supply Of Ear In Fetusesmentioning
confidence: 54%
See 3 more Smart Citations
“…A number of studies carried out on the vascularization of middle ear did not report the presence of stapedial artery; however, its presence was determined in this study and some other studies on certain mammal species like a mongolian gerbil (Rosowski et al, 1999), rats (Ortug, 2001;Yamamoto et al, 2003), fossorial rodents (Lange et al, 2004), and Talpid moles (Mason, 2006). Lange et al (2004) and Ortug (2001) observed that stapedial artery passing through intercrural foramen was surrounded by an osseous canal. Ortug (2001) also reported that the artery continued in such a canal in the middle ear cavity after exiting from the foramen.…”
Section: Anatomy and Arterial Supply Of Ear In Fetusesmentioning
confidence: 54%
“…Cochlea was determined to make 3.25-3.5 turns in bovine fetuses examined in the study, which was surprisingly more compatible with the results reported for guinea pigs, cats, and dogs than adult cattle. In addition, Lange et al (2004) reported that cochlear spiral number appeared not directly related to hearing ability, but when examined more closely, subterranean mammals were found to have more spiral formation than their epigeic relatives (rat, mouse etc.). Subterranean mammals were normally expected to have better hearing ability (Webster, 1966); however, spiral number was found higher in aboveground mammals both in this study and the previous ones (Wysocki, 2001), which supported the idea that hearing ability was not related to spiral number.…”
Section: Anatomy and Arterial Supply Of Ear In Fetusesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some authors have associated the shape of the bulla of different mammalian species to idealised geometric figures in order to calculate the bullar volume from external measurements; such figures include, for example, the cylinder (Lange et al, 2004), the rectangular prism (Huang et al, 2002;Lange & Burda, 2005), or the elliptical cone (Schleich & Vassallo; Begall & Burda; Francescoli et al). However, a comparison between the different methods employed has never been performed, nor is available a detailed study of the relationship between this type of estimations and the real tympanic volume.…”
Section: Introductionmentioning
confidence: 99%